Applying systems ergonomics methods in sport: A systematic review. (October 2019) - Hulme, Adam; Thompson, Jason; Plant, Katherine L.; Read, Gemma J.M.; Mclean, Scott; Clacy, Amanda; Salmon, Paul M.
Abstract: Introduction: As sports systems become increasingly more complex, competitive, and technology-centric, there is a greater need for systems ergonomics methods to consider the performance, health, and safety of athletes in context with the wider settings in which they operate. Therefore, the purpose of this systematic review was to identify and critically evaluate studies which have applied a systems ergonomics research approach in the context of sports performance and injury management. Material and methods: Five databases (PubMed, Scopus, ScienceDirect, Web of Science, and SPORTDiscus) were searched for the dates 01 January 1990 to 01 August 2017, inclusive, for original peer-reviewed journal articles and conference papers. Reported analyses were underpinned by a recognised systems ergonomics method, and study aims were related to the optimisation of sports performance (e.g. communication, playing style, technique, tactics, or equipment), and/or the management of sports injury (i.e. identification, prevention, or treatment). Results: A total of seven articles were identified. Two articles were focussed on understanding and optimising sports performance, whereas five examined sports injury management. The methods used were the Event Analysis of Systemic Teamwork, Cognitive Work Analysis (the Work Domain Analysis Abstraction Hierarchy), Rasmussen's Risk Management Framework, and the Systems Theoretic Accident Model and Processes method. The individual sport application was distance running, whereas the team sports contexts examined were cycling, football, Australian Football League, and rugby union. Conclusions: The included systems ergonomics applications were highly flexible, covering both amateur and elite sports contexts. The studies were rated as valuable, providing descriptions of injury controls and causation, the factors influencing injury management, the allocation of responsibilities for injury prevention, as well as the factors and their interactions underpinning sports performance. Implications and future directions for research are described. Highlights: There is a growing body of systems ergonomics research in the context of sports performance and injury management. Systems ergonomics methods in sport attempt to consider the performance, health, and safety of the individual athlete in context with the wider settings that surround them. This systematic review reports on the purpose, contexts, outcomes, and study quality of the identified sports systems ergonomics applications. Further systems ergonomics applications in sport are required to better understand the full range of factors underpinning sports performance and injury management.